(3GdReQOI aj GdehGYX hGdRgOs - (3GdbQWHj, GdCfOdSj, CHh YeQ, CMeO Hf eMeO Hf YHO QHg, J (B328(3g`s
(3ChdgG (B:s
(3aQT cJGH GdehGYX hGdRgO(B. (3bGd CMeO Hf eMeO Hf YHO QHg bO eVi bhdfG aj GdCeKGd hfMf bGFdhf HYhf Gddg hJhajbg aj GdRgO hQLGdg(B...s
(3BNQgG (B:s
(3cd TjA bGJd Mjf Jdbi CLdc(B. (3Je GdcJGH GdChd ef GdReQOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B207s
(3cTa GdXfhf(B: (3L(B2(3, (B1149s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs